1989
DOI: 10.1007/bf01317926
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans cells in vaccinia virus infection in mouse skin

Abstract: Langerhans cells function as potent antigen-presenting cells in the epidermis. They were shown to play an essential role in the mechanisms of defense of the skin against viral infections. In the present study, the response of Langerhans cells to infection of the skin with vaccinia virus was investigated. Decrease in Langerhans cell density in the skin was accompanied by an increase in the pathogenicity of the WR and Noguchi but not of the Lister strain of vaccinia virus. Langerhans cell density was shown to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…There is an inverse correlation between LC density at the site of infection and the severity of herpes simplex virus type 1 infections (36,37). A similar relationship was observed with vaccinia virus, where infection is more severe when the virus is inoculated into LC-depleted skin (3). A number of studies have shown that LC are depleted in dysplastic cervical tissue (31,41).…”
mentioning
confidence: 62%
“…There is an inverse correlation between LC density at the site of infection and the severity of herpes simplex virus type 1 infections (36,37). A similar relationship was observed with vaccinia virus, where infection is more severe when the virus is inoculated into LC-depleted skin (3). A number of studies have shown that LC are depleted in dysplastic cervical tissue (31,41).…”
mentioning
confidence: 62%
“…Here also, vaccinia virus infection was found to be more severe when the virus was inoculated into a skin area depleted in Langerhans cells than when it was injected into a normal skin area [7]. These results are particularly significant in view of the research efforts that have been pursued so intensively during the last years in the design of novel recombinant vaccines using vaccinia virus as a polyvalent vector [17,149].…”
Section: Role Of Dendritic Cells In the Control Of Primary Viral Infementioning
confidence: 91%
“…This is illustrated by the case report of a young asymptomatic HIV-infected US military recruit who developed severe disseminated vaccinia infection following routine vaccination against smallpox [ 109]. Residual pathogenicity of genetically engineered vaccinia virus strains will therefore represent a major source of concern in the use of these vectors for largescale vaccination [7,109]. However, epidermal Langerhans cell depletion may not affect the virulence of all vaccinia virus strains to the same degree, suggesting the need for testing the effect of Langerhans cell elimination on the pathogenicity of vaccinia virus strains prior to their use as vaccine carriers [7].…”
Section: Role Of Dendritic Cells In the Control Of Primary Viral Infementioning
confidence: 95%
See 2 more Smart Citations